ANALISA VARIASI JUMLAH LILITAN PADA ALAT PENGHEMAT BAHAN BAKAR TERHADAP EMISI GAS BUANG MOTOR BENSIN 4 LANGKAH - Pratama PEP; Digdo Listyadi (ROTOR, 2014)
Process combustion of fuel in room burn to be influenced by many factor , among others is temperature, closeness of mixture, composition, and turbulensi exist in mixture. When fuel temperature with air mount, hence will progressively easy  to  fuel with  the air  to on  fire.Gas emission  throw away which  is yielded  from combustion  process  at motor  vehicle  can  have  the  character  of  poison  and make  negative  effect  at environment around, the mentioned in causing by less perfect combustion process, gas result of less the combustion perfect for example is CO, HC.The purpose of this study was to determine the effect of the use of electromagnets  in  the  fuel  line gasolin engine 4 step with variations  in  the number of windings on exhaust emissions and  fuel consumption  . The study was conducted  in Laboratory Convert Energi Majors Technical Engineering Faculty Of Technique University Jember . Equipments which  is used  in  the  testing  is Motor gasoline 4 Step with machine brand Honda Supra x  125D, Gas Analyzer , buret, measure glass,  stop wach, tachometer , and accumulator 12 volt. used by materials is Premium RON 88, strand of metal  have diameter to 0,6 cm, pipe  have diameter to 1" with length 12 cm, and ring 18 cm.This study focuses on the variation of the number of windings on fuel saving devices on exhaust emissions of petrol 4 step. Analysis of the data sought includes AFR, Magnetic Field, Ampere each variation, emissions of CO gas (%), CO2 emissions (%), HC emissions (ppm), O  gas emissions (%). Fuel Consumption (FC). From the research  2conducted,  it can be concluded  that  the  larger  the number of winding electromagnets,  the more binding  the amount of oxygen in the combustion chamber , so it would be more optimal combustion. The lower the value of the FC (Fuel Consumtion), the lower the fuel consumption required for the performance of the engine. Variations in the amount of electromagnetic windings affect fuel consumption  . Fuel consumption is  the most efficient use of  the variation  found  in  the number of windings of  the coil 1000  fuel standard state conditions of 0.57 Kg / hr to 0.43 Kg / h at 3000 RPM rotation with increased efficiency of about 8.14% . Although these results are smaller than the results of previous research by 20.35 % , but at engine speed 9000 RPM FC  results of  this  study  resulted  in a  lower ,  ie 0.81 Kg  / hour compared  to 1.19 Kg  / hour.   Keywords : Magnetic Field, Emission Gas  throw away  , Fuel Consumtion.